Who is Chloe Kim? - Loh, Stefanie; Gutierrez, Manuel 1975- (New York : Penguin Workshop, 2022)
"Learn about the life and career of Olympic gold medalist and legendary snowboarder Chloe Kim"
Timelines.
Includes bibliographical references (pages 49).
Keywords: Kim, Chloe, -- 2000- -- Juvenile literature; Women snowboarders -- United States -- Biography -- Juvenile literature; Snowboarders -- United States -- Biography -- Juvenile literature; Women Olympic athletes -- United States -- Biography -- Juvenile literature; Olympic athletes -- United States -- Biography -- Juvenile literature; Biographies